2010
DOI: 10.5037/jomr.2010.1306
|View full text |Cite
|
Sign up to set email alerts
|

Gingival Squamous Cell Carcinoma: a Case Report

Abstract: BackgroundSquamous cell carcinoma is a malignant epithelial neoplasm characterized by variable clinical manifestations. When located in the gingiva, this neoplasm may mimic common inflammatory lesions. The aim of this study was to report a case of atypical squamous cell carcinoma, in which the patient had no risk factors for the development of this neoplasm.MethodsA 61 year old Caucasian female was seen with a 3 month history of a rapidly growing, painful nodule in the gingiva adjacent to tooth #11. Clinical e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 16 publications
0
17
1
1
Order By: Relevance
“…1 Tumor of upper alveolar ridge and hard palate is not very common with upper gingival cancers constituting nearly 3.5% of all oral malignancies, age of presentation mainly in 4 th -5 th decade. 1,2 The risk factors are alcohol and tobacco both of which act as local irritants to the mucosa. 3 In India these are among the top fi ve cancers and highest among woman because of habitual betel nut chewing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 Tumor of upper alveolar ridge and hard palate is not very common with upper gingival cancers constituting nearly 3.5% of all oral malignancies, age of presentation mainly in 4 th -5 th decade. 1,2 The risk factors are alcohol and tobacco both of which act as local irritants to the mucosa. 3 In India these are among the top fi ve cancers and highest among woman because of habitual betel nut chewing.…”
Section: Discussionmentioning
confidence: 99%
“…The disproportionately higher prevalence of head and neck neoplasm in India may be due to the use of tobacco in various forms. 1,2 The incidence is two to three times more frequent in men than women owing to increased tobacco abuse. 2 Gingivobuccal sulcus, hard palate and maxilla are uncommon and diagnosed at an advanced stage due to delay in presentation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is uncommon for an aphthous ulcer to present on the attached gingiva but such cases have been documented in the literature. [18] Earlier studies on GSCC have reported the lesion on posterior mandible,[16192021] posterior maxilla,[1422] anterior maxilla[1523] and anterior mandible. [24] To the best of our knowledge, this is the first case report on the above mentioned anatomic location.…”
Section: Discussionmentioning
confidence: 99%
“…La manifestación clínica es variada, en estadíos tempranos se puede observar una lesión leucoplá-sica, eritroplásica, leucoeritroplásica o una úlcera pequeña asintomática. En etapas más avanzadas puede presentarse como masa exofítica o endofítica, con borde irregular, indurada y de fondo sucio 12,13 . El diagnóstico temprano es difícil debido a la poca sintomatología que presenta, esto provoca que la mayoría de los pacientes consulten cuando las lesiones han alcanzado gran tamaño, siendo entonces el tratamiento más complicado y el pronóstico peor 14 .…”
Section: Sobrevida En Carcinoma Espinocelular De Mucosa Oral: Análisiunclassified